HUBUNGAN DUKUNGAN KELUARGA TERHADAP HARGA DIRI PASIEN ALOPESIA POST KEMOTERAPI DI RSUD ARIFIN ACHMAD - Putra " Ananda; Nurul " Huda; Gamya Tri Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstrack The purpose of this research is to examine the relationship between family support for the alopecia patient's dignity. This research uses descriptive correlation  research design with cross sectional approach. These samples included 76 respondents drawn based on inclusion criteria using purposive sampling techniques and chi square test. The results based on the respondents characteristics, shows the majority are mid adulthood (26-45 years) as many as 45 people (59.2%), the majority of respondents are female as many as 53 people (69.7%), the majority of respondents are married status as 68 (89.5%) with the majority of families who accompany respondents are husband / wife as many as 51 people (67.1%), the majority of respondents ever undergone chemotherapy to 3 of 20 people (26,3%) and chemotherapy to 4 is 20 people (26,3%) and the majority of the 76 respondents who do not use the veil is as many as 40 people (60.5%). The majority of respondents who have hight family support amounted to 44 (57.9%) and the majority of respondents who have hight dignity as many as 43 people (56.6%). Statistical test results between family support for the alopecia patient's dignity which obtained p value (0.00) < α (0.05) so that it can be concluded there is a significant correlation between family support to post chemotherapy patient’s dignity. The results of this study recommends that families can be a support system to provide motivation and encouragement that as to facilitate and provide information on the treatment of hair loss experienced by alopecia patien’s.  Keywords  : Alopecia, cancer, dignity, family support Reference  :68 (2005-2016)